Determination of Job Satisfaction: Analysis of Self-Efficacy, Work Motivation and Work Environment (Garment In Indonesia) - Didin Sjarifudin; Hapzi Ali (Dinasti Publisher, 2023)
The purpose of the study is to prove and provide an overview of the variables in this study for the garment industry, especially at the level of managers and supervisors This research methodology uses a qualitative approach and examines the variables of this study. A type or method of academic writing is in the form of library research. Theoretical analysis, analysis of relationships between variables, books and journals, online and offline, were obtained from Mendeley, Google Scholar and other online media. The results showed that the object of the garment industry for managers and supervisors who run company management with the results there is a positive and significant influence from various scientific articles originating from reputable national and international journals, and there are several distinguishing variables that can be used later in future research, namely competence, job performance, perceived influence or work relations ship, work load, Organizational Performance and public service.